Relationship Of Parent Communication With Temper Tantrum In Preschool Children (Ages 3-6 Years) In Paud Buah Hati Mother And State 01 Sitiung Year 2020 - Sri Fawziyah; Erma Erfiana (Science Midwifery, 2022)
Tantrum temper is an uncontrolled outburst of emotions or anger caused by an unpleasant atmosphere the child feels, is a disorder of behavior in preschoolers, which is part of the emotional development process of the child. Factors causing temper tantrums are physiological, psychological, parental (communication and parenting) and environmental factors. Effective communication is one of the appropriate handling measures in reducing the incidence of temper tantrums in preschool children. The purpose of this study was to determine the relationship of parental communication with temper tantrums in preschool children (ages 3-6 years) in Paud Buah Hati Bunda and Negeri 01 Sitiung in 2020. The research method used Observational research is Analytical Inferential Hypothesis. The sampling technique used is total sampling with a population of 92 respondents and a total sample of 50 respondents. Analysis of the data used chi square test using SPSS. The results showed that out of 38 people (76%) of respondents the communication between parents was quite large, 34 people (68%) were at risk of temper tantrums and a small portion of 4 people (8%) were not at risk of temper tantrums. Based on statistical test results obtained, p value = 0.000 = 0.05. So that it can be concluded that there is a significant relationship between parental communication with temper tantrums in preschool children (ages 3-6 years) in Paud Buah Hati Bunda and Negeri 01 Sitiung in 2020. It is hoped that the results of this study will be able to communicate well using effective communication and knowing how to deal with temper tantrums